THE EFFECT OF CORPORATE SOCIAL RESPONSIBILITY, PROFITABILITY, AND LEVERAGE ON FIRM VALUE WITH FIRM SIZE AS A MODERATING VARIABLE - Puspasari, Marchsyta Dwi; Haryati, Tantina (Yayasan Education and Social Center, 2023)
This study examines the moderating effects of CSR, profitability, and leverage on firm value and the impact of fit Size in moderating these effects. In this quantitative research, the purposive sampling technique determined 22 energy-related companies listed on the Indonesia Stock Exchange during the 2019-2022 period. Partial least squares were used to analyze the data in this study, with analysis performed in SmartPLS 3.0. This study concludes that CSR and firm Size do not affect substantial value, but profitability and leverage positively and significantly affect significant value. Fit Size as a moderating variable successfully moderates the effect of CSR and power on firm value but cannot reconcile the impact of profitability on solid value. The implications of this study's result for companies are substantial since they may be used to investigate and address the factors that affect significant value as reflected by stock prices